External Financial Aid to Blood Transfusion Services in Sub-Saharan Africa: A Need for Reflection - Ala, Fereydoun (Public Library of Science, 2012)
Jean-Pierre Allain and colleagues argue that, while unintended, the foreign aid provided for blood transfusion services in sub-Saharan Africa has resulted in serious negative outcomes, which requires reflection and rethinking.